Ammonia recovery from anaerobic digestate: State of the art, challenges and prospects - Yang, D.; Chen, Q.; Liu, R.; Song, L.; Zhang, Y.; Dai, X.
Nitrogen-containing wastewater and organic wastes are inevitably produced during human activities. To reduce nitrogen pollution, much energy has been used to convert ammonia nitrogen into nitrogen gas through biological nitrogen removal method. However, it needs to consume high energy again during industrial nitrogen fixation, which give rise to massive greenhouse gas (GHG)emissions. Therefore, ammonia recovery from organic wastes has attracted much attention in recent years. In this review, the advantages and disadvantages of ammonia stripping, membrane separation and struvite precipitation are discussed firstly. The ammonia stripping mechanisms, influencing factors, mass transfer process, and the latest innovative ammonia stripping techniques from the anaerobic digestate of organic wastes are critically reviewed. Additionally, a comprehensive economic analysis of different ammonia removal or recovery processes is carried out. The challenges and prospects of ammonia recovery are suggested. Ammonia recovery is of great significance for promoting nitrogen cycle, energy saving and GHG emission reduction.
Keywords: ANAEROBIC DIGESTATE; AMMONIA RECOVERY; VACUUM AMMONIA STRIPPING; MASS TRANSFER; ECONOMIC ANALYSIS